2002
DOI: 10.1016/s1074-7613(02)00389-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood Dendritic Cells Interact with Splenic Marginal Zone B Cells to Initiate T-Independent Immune Responses

Abstract: Marginal zone (MZ) and B1 B lymphocytes participate jointly in the early immune response against T-independent (TI) particulate antigens. Here we show that blood-derived neutrophil granulocytes and CD11c(lo) immature dendritic cells (DC) are the primary cells that efficiently capture and transport particulate bacteria to the spleen. In a systemic infection, CD11c(lo) DC, but not neutrophils, provide critical survival signals, which can be inhibited by TACI-Fc, to antigen-specific MZ B cells and promote their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
458
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(488 citation statements)
references
References 36 publications
28
458
0
2
Order By: Relevance
“…injection of particulate Ag (20). We found increased expression of syndecan I on WT MZB cells as early as 16 h after infection, but by 24 h, this marker was no longer detected (Fig.…”
Section: B Hermsii Infection Activates Mzb Cellsmentioning
confidence: 70%
See 1 more Smart Citation
“…injection of particulate Ag (20). We found increased expression of syndecan I on WT MZB cells as early as 16 h after infection, but by 24 h, this marker was no longer detected (Fig.…”
Section: B Hermsii Infection Activates Mzb Cellsmentioning
confidence: 70%
“…Dendritic cells can capture Ag and transport them to the spleen where they interact with MZB cells to initiate T-independent immune responses (20). However, marginal zone macrophages probably play a lesser role, because their depletion has been shown to increase humoral responses to TI-2 Ag (9).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that BAFF may be produced by DC and other cells in response to pathogens to promote rapid production of protective Ab. Indeed, Balazs et al [14] found that the rapid Ab response to S. pneumoniae in mice is mediated by blood DC, which bind bacteria, migrate to splenic marginal zones (MZ) and promote antigen-specific MZ B cell Ab production through a BAFF-dependent mechanism. Consistent with this model, we and others have found that mouse and human DC promote B cell proliferation in vitro by secreting BAFF.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, DC-derived cytokines also promoted B cell proliferation and switching to IgA, independent of CD40; however, this was mediated through BAFF and APRIL (17,18), which also support plasmablast survival in vivo (19). The kinetics of the response suggest that DC-derived IFN-b and TNF-a play important roles in the early phase of humoral immunity.…”
Section: Discussionmentioning
confidence: 76%
“…This is important for the development of safe and efficient vaccination strategies that reduce the burden of C. jejuni-induced disease, including the development of serious sequelae like GBS. Because myeloid cells, such as DCs, are important for bridging innate and adaptive immunity, as well as play an important role in the development of humoral immunity to T-independent Ags (17)(18)(19), we previously investigated the potential of DCs stimulated with C. jejuni LOS to promote B cell responses. It was shown that human monocyte-derived DCs stimulated with C. jejuni LOS produce soluble factors that enhance B cell proliferation, independently of T cells (14).…”
mentioning
confidence: 99%